Metaproteomic analysis from cervical biopsies and cytologies identifies proteinaceous biomarkers representing both human and microbial species - Faktor, Jakub; Henek, Tomas; Hernychova, Lenka; Singh, Ashita; Vojtesek, Borek; Polom, Joanna; Bhatia, Ramya; Polom, Karol; Cuschieri, Kate; Cruickshank, Margaret; Gurumurthy, Mahalakshmi; Goodlett, David R; et al. (Talanta, 2024)
The detection of HPV infection and microbial colonization in cervical lesions is currently done through PCR-based viral or bacterial DNA amplification. Our objective was to develop a methodology to expand the metaproteomic landscape of cervical disease and determine if protein biomarkers from both human and microbes could be detected in distinct cervical samples. This would lead to the development of multi-species proteomics, which includes protein-based lateral flow diagnostics that can define patterns of microbes and/or human proteins relevant to disease status. In this study, we collected both non-frozen tissue biopsy and exfoliative non-fixed cytology samples to assess the consistency of detecting human proteomic signatures between the cytology and biopsy samples. Our results show that proteomics using biopsies or cytologies can detect both human and microbial organisms. Across patients, Lumican and Galectin-1 were most highly expressed human proteins in the tissue biopsy, whilst IL-36 and IL-1RA were most highly expressed human proteins in the cytology. We also used mass spectrometry to assess microbial proteomes known to reside based on prior 16S rRNA gene signatures. Lactobacillus spp. was the most highly expressed proteome in patient samples and specific abundant Lactobacillus proteins were identified. These methodological approaches can be used in future metaproteomic clinical studies to interrogate the vaginal human and microbiome structure and metabolic diversity in cytologies or biopsies from the same patients who have pre-invasive cervical intraepithelial neoplasia, invasive cervical cancer, as well as in healthy controls to assess how human and pathogenic proteins may correlate with disease presence and severity.
Keywords: dospělí; Female; Lactobacillus; galektin 1; biologické markery; Biomarkers; Lumican; Adult; ženské pohlaví; biopsie; cervix uteri; lidé; proteomika; Microbiota; nádory děložního čípku; Galectin 1; Proteomics; mikrobiota; lumican; Biopsy; Uterine Cervical Neoplasms; Cervix Uteri; Humans